1996
DOI: 10.1177/00220345960750090901
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of Tooth Enamel in Recessive Dystrophic Epidermolysis Bullosa: Significance with Respect to Dental Caries

Abstract: Previous reports have linked the prevalence of tooth abnormalities with high caries experience in the different types of epidermolysis bullosa (EB). However, it is not known to what extent the apparent susceptibility to enamel caries is due to disease-related altered enamel chemistry in these cases. The aim of this study was to characterize the enamel of teeth from patients suffering from recessive epidermolysis bullosa dystrophica (rEBD) in terms of its mineral content, carbonate content, protein content, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Minor enamel defects have been shown to occur in all EB subtypes, with the most substantial occurring in the EBJ subgroup. [87][88][89][90] All patients with EDJ have been reported to present with defects in enamel, whereas the prevalence of defects in EBS and EBD was similar to that of the control population (27%), suggesting that the mechanism causing damage to enamel may be very different between the three subtypes. 88 In addition, Wright et al 88 reported that the incidence of dental caries was increased in patients with EBJ and EBD.…”
Section: Epidermolysis Bullosamentioning
confidence: 99%
See 1 more Smart Citation
“…Minor enamel defects have been shown to occur in all EB subtypes, with the most substantial occurring in the EBJ subgroup. [87][88][89][90] All patients with EDJ have been reported to present with defects in enamel, whereas the prevalence of defects in EBS and EBD was similar to that of the control population (27%), suggesting that the mechanism causing damage to enamel may be very different between the three subtypes. 88 In addition, Wright et al 88 reported that the incidence of dental caries was increased in patients with EBJ and EBD.…”
Section: Epidermolysis Bullosamentioning
confidence: 99%
“…Studies into the chemical composition of enamel from EB patients, in terms of mineral content, carbonate content, protein content and amino acid composition, have reported essentially normal enamel chemistry in EBD patients whereas EBJ enamel contained a significantly reduced mineral per volume content, which resulted in enamel hypoplasia. 87,89 The high caries incidence in EBD patients may be related to other factors such as compromised oral hygiene, whereas in EBJ patients the enamel is developmentally compromised and associated with the genetic basis of the disease. In contrast, other workers have reported minor enamel defects in all three EB subtypes with a slight reduction (10%) in mineral content in some EBJ and EBD teeth.…”
Section: Epidermolysis Bullosamentioning
confidence: 99%
“…[7][8][9][10] Similarly, oral hard tissues may show either a marked developmentally compromised enamel or minor structural defects with areas of surface pitting and furrowing. [11][12][13][14][15] Although until now no consensus statement on EB severity score has been established, two reports have been published aimed at developing an EB scoring system. 16,17 These attempted to develop a method of scoring EB severity but evaluated too many variables (eg, skin, height, weight, mucous membranes, nutritional status, cancer) and gave little, if any, weight to the oropharyngeal component.…”
mentioning
confidence: 99%
“…4 Non-Herlitz junctional epidermolysis bullosa (nH-JEB) caused by COL17 deficiency shows the abnormal tooth formation of amelogenesis imperfecta. [5][6][7] We therefore hypothesized that COL17 in hemidesmosomes also plays an important role in mesenchymal-epithelial interactions in tooth formation.…”
mentioning
confidence: 99%